Muscle founder cells regulate defasciculation and targeting of motor axons in the Drosophila embryo. - Landgraf, M.; Baylies, M.; Bate, M. (Current Biology, 1999)
During Drosophila embryogenesis, motor axons leave the central nervous system (CNS) as two separate bundles, the segmental nerve (SN) and intersegmental nerve (ISN). From these, axons separate (defasciculate) progressively in a characteristic pattern, initially as nerve branches and then as individual axons, to innervate target muscles [1] [2]. This pattern of branching resembles the outgrowth and defasciculation of motor axons from the neural tube of vertebrate embryos. The factors that trigger nerve branching are unknown. In vertebrate limbs, the branched innervation may depend on mesodermal cues, in particular on the connective tissues that organise the muscle pattern [3]. In Drosophila, the muscle pattern is organised by specific mesodermal cells, the founder myoblasts, which initiate the development of individual muscles [4][5][6]. Founder myoblasts fuse with neighbouring non-founder myoblasts and entrain these to a specific muscle programme, which also determines their innervation [4] [7]. In the absence of mesoderm, ISN and SN can form, but motor axons fail to defasciculate from these bundles [7]. The cue(s) for nerve branching therefore lie within the mesoderm, most likely in the muscles and/or in the precursor cells of the adult musculature [8]. Here, we show that founder myoblasts are the source of the cue(s) that are required to trigger defasciculation and targeted growth of motor axons. Moreover, we found that a single founder myoblast can trigger the defasciculation of an entire nerve branch. This suggests that the muscle field is structured into sets of muscles, each expressing a common defasciculation cue for a particular nerve branch.